Olahraga Sebagai Sarana Penguat Interaksi Sosial: Studi Pada Perayaan Dies Natalis UNM - Hudain, Muh. Adnan; Fatoni, Fatoni; Suwardi, Suwardi; Badaru, Benny (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to examine the role of sports as a means of strengthening social interaction in the anniversary celebrations of Universitas Negeri Makassar (UNM). Using a descriptive qualitative approach, data were collected through participant observation, in-depth interviews with 20 informants, and documentation of activities. The results show that sports play a significant role in building cooperation, solidarity, and social networks among campus residents, including students, lecturers, and educational staff. Sports activities are not only a means of competition but also an effective social communication space in strengthening collective identity and a sense of belonging to the institution. These findings underscore the importance of institutional sports activities as a strategy to increase social cohesion and shape an inclusive and participatory campus culture